Trematode parasites infect or die in snail hosts. - King, K; Jokela, J; Lively, C (2011)
The Red Queen hypothesis is based on the assumption that parasites must genetically match their hosts to infect them successfully. If the parasites fail, they are assumed to be killed by the host's immune system. Here, we tested this using sympatric (mostly susceptible) and allopatric (mostly resistant) populations of a freshwater snail and its trematode parasite. We determined whether parasites which do not infect are either killed or passed through the host's digestive tract and remain infectious. Our results show that parasites do not get a second chance: they either infect or are killed by the host. The results suggest strong selection against parasites that are not adapted to local host genotypes.